2023
DOI: 10.1007/s40544-022-0690-x
|View full text |Cite
|
Sign up to set email alerts
|

Metastable hybridized structure transformation in amorphous carbon films during friction—A study combining experiments and MD simulation

Abstract: Amorphous carbon films have attracted substantial interest due to their exceptional mechanical and tribological properties. Previous studies revealed that the amorphous carbon films exhibited lower coefficient of friction (COF) because of the transformation in bond structure from sp3-C to sp2-C during friction processes. However, the mechanism for such a transformation during friction is not well understood. This study is conducted to get an insight into the metastable transformation in amorphous carbon film d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that under high contact stress, MoS 2 can decompose into molybdenum and sulfur atoms from a molecular dynamics perspective. Additionally, the catalytic effect of Mo atoms and stress‐induced chemical reactions can promote the transformation of amorphous carbon to an ordered graphene band structure 39,40 . In this experiment, the increasing load results in high contact stress, which accelerates the graphitization transformation to an ordered graphene band structure.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown that under high contact stress, MoS 2 can decompose into molybdenum and sulfur atoms from a molecular dynamics perspective. Additionally, the catalytic effect of Mo atoms and stress‐induced chemical reactions can promote the transformation of amorphous carbon to an ordered graphene band structure 39,40 . In this experiment, the increasing load results in high contact stress, which accelerates the graphitization transformation to an ordered graphene band structure.…”
Section: Resultsmentioning
confidence: 92%
“…37 The G peak is located around 1610 cm À1 . 38 To obtain more information, we calculated the 39,40 In this experiment, the increasing load results in high contact stress, which accelerates the graphitization transformation to an ordered graphene band structure. This phenomenon is consistent with the Raman characterization of the transfer film's carbon characteristic peaks.…”
Section: Frictional Wear Mechanismmentioning
confidence: 99%
“…With the development of computer technology and highthroughput calculations, density functional theory (DFT) simulations have been widely applied to study the adhesion and friction mechanism of the contact or sliding interface. [15][16][17] Feldbauer et al 18 investigated the adhesion and material transfer between Al and TiN contacting surfaces based on DFT theory. They observed the transfer of the material from an Al slab towards a TiN slab for the interfacial configurations, which exhibited a larger adhesion energy than the energy cost to remove layers from the Al slab.…”
Section: Introductionmentioning
confidence: 99%
“…10−13 The relationship between the microstructure and tribological properties largely determines the application and design of a-C films. 14 The complex three-dimensional network structure of a-C films, which consists of sp 3 and sp 2 hybridization, leads to their metastable structural transformation during the sliding process, depending on factors such as the sp 2 /sp 3 ratio, 15,16 interaction with lubricating oil, 17,18 and residual stress. 19,20 These structural transformations are sensitive to the contact pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between the microstructure and tribological properties largely determines the application and design of a-C films . The complex three-dimensional network structure of a-C films, which consists of sp 3 and sp 2 hybridization, leads to their metastable structural transformation during the sliding process, depending on factors such as the sp 2 /sp 3 ratio, , interaction with lubricating oil, , and residual stress. , These structural transformations are sensitive to the contact pressure. , Hetzner et al investigated the friction behavior of hydrogenated a-C films subjected to high contact pressures of 1–3 GPa and different counter materials. It was found that when the a-C film and a steel sheet were used as a friction pair, the film quickly failed because of adhesion and antibody steel transfer.…”
Section: Introductionmentioning
confidence: 99%